Lactate dynamics responses during a triathlon season in young triathletes - Kislev-Cohen, R.; Zigel, L.; Navot, D.; Zilberman, U.; Shargal, E. (The 3rd Wingate Congress of Exercise and Sport Sciences, 2014)
Background: The triathlon is a sport consisting of sequential swimming, cycling and running. Although race distances vary, triathlons of all distances can be considered to be endurance events. Physiological measurements at sub-maximal workloads, such as lactate response, have been shown to be important determinants of endurance ability and valuable indicators of performance. Changes in blood lactate dynamics during a triathlon session can give valuable feedback to the coach as well as to the athletes about their training adaptations and response.